2019
DOI: 10.5152/tud.2018.96237
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian metastasis of renal cell carcinoma: Clinical and pathological presentation of a case

Abstract: A 82-year-old woman was referred to our hospital with complaints of weight loss, loss of appetite, abdominal pain and a palpable pelvic mass. Abdominal imaging revealed a tumour at the upper pole of the right kidney with a maximum diameter of 8 cm and a second tumour in the pelvis, mostly solid, with a maximum diameter of 16 cm, that seemed to originate from the left ovary. As she was initially considered to have two distinct tumours, through a single transabdominal incision, she simultaneously underwent right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Our nomogram highlighted the fact that the rate of distant metastasis increased with the RCC differentiation (from well to poorly differentiated). Other reports similarly showed that poor pathological differentiation of RCC was correlated with inferior prognosis (45)(46)(47). This is not surprising, as the pathological differentiation grade reflects the tumor biological behavior and represents an independent predictor for distant RCC metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…Our nomogram highlighted the fact that the rate of distant metastasis increased with the RCC differentiation (from well to poorly differentiated). Other reports similarly showed that poor pathological differentiation of RCC was correlated with inferior prognosis (45)(46)(47). This is not surprising, as the pathological differentiation grade reflects the tumor biological behavior and represents an independent predictor for distant RCC metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…However, a recent literature review of 41 cases by Koufopoulos et al [6] revealed nearly equal occurrence in the left (49%) versus right (51%) renal origins of ovarian metastasis. In the setting of bilateral ovarian masses and a renal mass, renal metastasis from a primary ovarian cancer can also be considered although this is considerably less common [14].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the major cause of cancer-related deaths and targeting this process has been proposed as a strategy to fight cancer [45]. Dai et al investigated the antimetastatic effect of total flavonoids of S. barbata (TF-SB).…”
Section: Liver Cancermentioning
confidence: 99%